A high resistivity sintered NdFeB permanent magnet material and preparation method thereof
By using specific raw materials and processes in sintered NdFeB permanent magnet materials, the resistivity and magnetic properties of the material are improved, and the problem of poor stability at high temperatures is solved, and the effect of simplifying the process and reducing costs is achieved.
Patent Information
- Application Number
- CN202411241795.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-09-05
AI Technical Summary
Sintered NdFeB permanent magnet materials lose their magnetic properties at high temperatures and have poor chemical stability, resulting in eddy current losses and thermal demagnetization, affecting their application stability. The existing methods increase in insulating materials or cutting magnets but affect magnetic properties and have complex and high cost.
Using base alloy fine powder, rare earth fluoride powder, antioxidants, lubricants and aviation gasoline, the high-resistance sintered NdFeB permanent magnet material is prepared through smelting, powder making, powder mixing, molding, sintering and aging treatment processes. , improve the resistivity and magnetic properties of the material.
It achieves high resistivity and excellent comprehensive magnetic properties, simplifies the preparation process, reduces cost and energy consumption, is suitable for large-scale production, and improves the temperature stability and coercivity of the material.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of permanent magnetic materials, and in particular to a high-resistivity sintered NdFeB permanent magnetic material and a preparation method thereof. Background Art
[0002] With the continuous advancement of science and technology, permanent magnet materials are increasingly used in industrial motors, white appliances, wind power generation and other fields. Among them, sintered NdFeB permanent magnet materials have become the most widely used rare earth permanent magnet materials due to their high magnetic energy product, high coercive force and high remanence. However, there are also some obvious problems in the use of sintered NdFeB permanent magnet materials, such as low temperature stability, easy to lose magnetism at high temperature, and weak chemical stability, which is easy to be corroded. These problems limit the application of sintered NdFeB permanent magnet materials in some special environments. In addition, permanent magnet motors will generate eddy current losses during service, resulting in temperature rise and thermal demagnetization. This thermal demagnetization is irreversible and cannot be re-magnetized, so the original magnetic flux cannot be guaranteed. Therefore, increasing the resistivity of sintered NdFeB permanent magnet materials and reducing eddy current losses are the key to improving their service stability.
[0003] At present, there have been some attempts to reduce the eddy current loss of sintered NdFeB permanent magnet materials by adding insulating materials or cutting the magnets into small pieces and then gluing them. However, these methods often have a great impact on the magnetic properties of the magnets, or the preparation process is complicated, the cycle is long, and the cost is high. For example, the Chinese invention patent with the authorization announcement number CN1048350C discloses a rare earth permanent magnet material with high insulation. The composition of the material is 1-10% epoxy resin, 0-10% polyvinyl butyral, 0-8% silane coupling agent, 0.5-10% epoxy polyester paint, and the rest is rare earth permanent magnet alloy powder. From the results, the electrical insulation performance has indeed been significantly improved, but the comprehensive magnetic properties of the magnet need to be further improved due to the addition of a large number of insulating additives.
[0004] It can be seen that how to provide a sintered NdFeB permanent magnet material that can not only improve resistivity but also maintain excellent comprehensive magnetic properties and has a simple preparation process is a difficult problem that needs to be solved urgently in the industry. Summary of the invention
[0005] The main purpose of the present invention is to provide a high-resistivity sintered NdFeB permanent magnet material with high resistivity and excellent comprehensive magnetic properties and a preparation method thereof.
[0006] To achieve the above object, the present invention provides a high resistivity sintered NdFeB permanent magnet material, which is prepared from the following raw materials in parts by mass: 95.0-99.9 parts of base alloy fine powder, 0.1-5 parts of rare earth fluoride powder, 0.1-0.3 parts of antioxidant, 0.2-1.2 parts of lubricant, and 0.2-5 parts of aviation gasoline; the composition of the base alloy fine powder is (PrNd) a (TM) b (HM) c Ga d B e Fe 100-a-b-c-d-e , 29.5≤a≤32.5, 0<b≤5, 0<c≤0.8, 0.3≤d≤0.5, 0.88≤e≤0.94, wherein TM is one or more of Al, Cu, Co, and Mn, and HM is one or more of Nb, Zr, Hf, Ti, and V.
[0007] Preferably, the raw materials for preparing the high resistivity sintered NdFeB permanent magnet material further include: 0.1-0.5 parts of nanomaterials.
[0008] Preferably, the nano material is at least one of nano tantalum silicide, nano niobium carbide, and nano ferrosoferric oxide; and the particle size of the nano material is 10-80 nm.
[0009] Preferably, the particle size of the rare earth fluoride powder is 1.0-3.0 μm.
[0010] Preferably, the rare earth fluoride is at least one of praseodymium fluoride, neodymium fluoride, dysprosium fluoride and terbium fluoride.
[0011] Preferably, the antioxidant is at least one of antioxidant 1010 and antioxidant 168.
[0012] Preferably, the lubricant is one or more of zinc stearate and magnesium stearate.
[0013] Another object of the present invention is to provide a method for preparing the high resistivity sintered NdFeB permanent magnet material, comprising the following steps:
[0014] Step S1, smelting: putting the base alloy powder into a smelting furnace according to the composition formula, and when the vacuum degree in the smelting furnace is ≤3Pa, smelting, pouring, and sieving to obtain a strip sheet with an average thickness of 0.285-0.305mm;
[0015] Step S2, powder making: placing the strips prepared in step S1 in a hydrogen crushing furnace, evacuating the vacuum, filling with hydrogen and crushing, dehydrogenating at 500-580°C for 5-7h to obtain coarse powder; then mixing the coarse powder with an antioxidant, and obtaining jet-milled fine powder of the base alloy by a jet milling process under nitrogen protection;
[0016] Step S3, powder mixing: the jet milled powder obtained in step S2 is uniformly mixed with rare earth fluoride powder, lubricant, aviation gasoline and nanomaterials, and then sieved by a sieving machine to reduce agglomeration of fine powder and improve the consistency of rare earth fluoride powder and nanomaterials at the grain boundary to obtain a mixed powder;
[0017] Step S4, molding: the mixed powder prepared in step S3 is pressed into a mold under a magnetic field, and isostatically pressed to obtain a compact;
[0018] Step S5, sintering: placing the compact produced in step S4 into a vacuum sintering furnace, and sintering at 1000-1050° C. for 6-12 hours to obtain a blank;
[0019] Step S6, aging: The blank produced in step S5 is subjected to a three-level aging treatment to obtain a high resistivity sintered NdFeB permanent magnet material.
[0020] Preferably, the smelting temperature in step S1 is 1455-1505°C.
[0021] Preferably, the pouring temperature in step S1 is 1405-1475°C.
[0022] Preferably, the average particle size of the jet-milled powder of the base alloy in step S2 is ≤2.8 μm, and D50 is ≤4.0 μm.
[0023] Preferably, the magnetic field strength of the magnetic field in step S4 is ≥ 2000 Gs.
[0024] Preferably, the isostatic pressing pressure in step S4 is 180-220 MPa, and the holding time is 5-60 s.
[0025] Preferably, the vacuum degree of the vacuum sintering furnace in step S5 is ≤0.05Pa.
[0026] Preferably, the first stage aging treatment temperature of the three-stage aging treatment in step S6 is 600-860°C, the time is 2-4h, the second stage aging treatment temperature is 360-600°C, the time is 2-4h, and the third stage aging treatment temperature is 450-510°C, the time is 2-4h.
[0027] Due to the application of the above technical solution, the present invention has the following beneficial effects:
[0028] (1) The method for preparing the high resistivity sintered NdFeB permanent magnet material disclosed in the present invention has a simple preparation process, convenient operation and control, no need for special equipment, low capital investment, low energy consumption, high preparation efficiency and finished product qualification rate, is suitable for continuous large-scale production, and has high promotion and application value.
[0029] (2) The high resistivity sintered NdFeB permanent magnet material disclosed in the present invention is prepared from the following raw materials in parts by weight: 95.0-99.9 parts of base alloy fine powder, 0.1-5 parts of rare earth fluoride powder, 0.1-0.3 parts of antioxidant, 0.2-1.2 parts of lubricant, and 0.2-5 parts of aviation gasoline; the composition of the base alloy fine powder is (PrNd) a (TM) b (HM) c Ga d B e Fe 100-a-b-c-d-e , 29.5≤a≤32.5, 0<b≤5, 0<c≤0.8, 0.3≤d≤0.5, 0.88≤e≤0.94, wherein TM is one or more of Al, Cu, Co, and Mn, and HM is one or more of Nb, Zr, Hf, Ti, and V. Through the interaction between the raw materials, the permanent magnetic material has high resistivity and excellent comprehensive magnetic properties; the F element with strong electron binding ability is introduced into the magnet by the rare earth fluoride powder to improve the overall resistance of the magnet; through the reasonable selection of the particle size of the air flow milling material of the base alloy and the screening by the screening machine, the rare earth fluoride powder and the nanomaterial are evenly distributed at the grain boundary of the thin zone, thereby further improving the resistivity of the material; in addition, the low temperature and long time sintering process is used to prevent the abnormal growth of grains during the sintering process, so that the increase in the amount of rare earth fluoride and nanomaterial added has less effect on the remanence of the permanent magnetic material, which is more conducive to the batch preparation of high-performance magnets. The comprehensive magnetic properties of permanent magnet materials can be effectively improved by rationally selecting the composition formula of base alloy fine powder.
[0030] (3) The high-resistivity sintered NdFeB permanent magnet material disclosed in the present invention, wherein the raw materials for preparing the high-resistivity sintered NdFeB permanent magnet material further include: 0.1-0.5 parts of nanomaterial; the nanomaterial is at least one of nano-tantalum silicide, nano-niobium carbide, and nano-ferroferric oxide. The addition of nanomaterials and the interaction with other raw material components can further improve the performance and resistivity of the permanent magnet material.
[0031] (4) The high resistivity sintered NdFeB permanent magnet material disclosed in the present invention has better comprehensive magnetic properties and higher resistivity through reasonable selection of preparation steps and process parameters; the agglomeration of rare earth-rich grain boundary phase can be reduced through three-level aging, so that the nanomaterials and rare earth fluorides dispersed at the grain boundaries are evenly distributed, and at the same time, the proportion of thin-area rich grain boundary phase that has a coercive force enhancement effect is increased, thereby improving the coercive force. DETAILED DESCRIPTION
[0032] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations. Example 1
[0033] A high resistivity sintered NdFeB permanent magnet material is prepared from the following raw materials in parts by mass: 95.0 parts of base alloy fine powder, 0.1 parts of rare earth fluoride powder, 0.1 parts of antioxidant, 0.2 parts of lubricant, and 0.2 parts of aviation gasoline; the composition of the base alloy fine powder is (PrNd) a (TM) b (HM) c Ga d B e Fe 100-a-b-c-d-e , a=29.5, b=5, c=0.1, d=0.3, e=0.88, where TM is Al and HM is Nb.
[0034] The raw materials for preparing the high resistivity sintered NdFeB permanent magnet material also include: 0.1 parts of nano material; the nano material is nano tantalum silicide; the particle size of the nano material is 10 nm.
[0035] The particle size of the rare earth fluoride powder is 1.0 μm; the rare earth fluoride is praseodymium fluoride; the antioxidant is antioxidant 1010; and the lubricant is zinc stearate.
[0036] A method for preparing the high resistivity sintered NdFeB permanent magnet material comprises the following steps:
[0037] Step S1, smelting: putting the base alloy powder into a smelting furnace according to the composition formula, and when the vacuum degree in the smelting furnace is ≤3Pa, smelting, pouring, and sieving to obtain a strip sheet with an average thickness of 0.285mm;
[0038] Step S2, powder making: placing the strips prepared in step S1 in a hydrogen crushing furnace, evacuating the vacuum, filling with hydrogen and crushing, and dehydrogenating at 500° C. for 5 hours to obtain coarse powder; then mixing the coarse powder with an antioxidant, and obtaining jet mill fine powder of the base alloy by a jet mill process under nitrogen protection;
[0039] Step S3, powder mixing: the jet milled powder obtained in step S2 is uniformly mixed with rare earth fluoride powder, lubricant, aviation gasoline and nanomaterials, and then sieved by a sieving machine to reduce agglomeration of fine powder and improve the consistency of rare earth fluoride powder and nanomaterials at the grain boundary to obtain a mixed powder;
[0040] Step S4, molding: the mixed powder prepared in step S3 is pressed into a mold under a magnetic field, and isostatically pressed to obtain a compact;
[0041] Step S5, sintering: placing the green compact produced in step S4 into a vacuum sintering furnace, and sintering at 1000° C. for 6 hours to obtain a green compact;
[0042] Step S6, aging: The blank produced in step S5 is subjected to a three-level aging treatment to obtain a high resistivity sintered NdFeB permanent magnet material.
[0043] The smelting temperature in step S1 is 1455°C; the pouring temperature in step S1 is 1405°C.
[0044] The average particle size of the jet-milled powder of the base alloy in step S2 is ≤2.3 μm, and D50 is ≤4.0 μm.
[0045] The magnetic field strength of the magnetic field in step S4 is ≥ 2000 Gs; the isostatic pressing pressure in step S4 is 180 MPa, and the holding time is 5 s; the vacuum degree of the vacuum sintering furnace in step S5 is ≤ 0.05 Pa.
[0046] The first stage of the three-stage aging treatment in step S6 is performed at a temperature of 600° C. for 2 h, the second stage is performed at a temperature of 360° C. for 2 h, and the third stage is performed at a temperature of 450° C. for 2 h. Example 2
[0047] A high resistivity sintered NdFeB permanent magnet material is prepared from the following raw materials in parts by mass: 96 parts of base alloy fine powder, 1.5 parts of rare earth fluoride powder, 0.15 parts of antioxidant, 0.4 parts of lubricant, and 1.5 parts of aviation gasoline; the composition of the base alloy fine powder is (PrNd) a (TM) b (HM) c Ga d B e Fe 100-a-b-c-d-e , a=30, b=1, c=0.2, d=0.35, e=0.9, where TM is Cu and HM is Zr.
[0048] The raw materials for preparing the high resistivity sintered NdFeB permanent magnet material also include: 0.2 parts of nano material; the nano material is nano niobium carbide; the particle size of the nano material is 30 nm.
[0049] The particle size of the rare earth fluoride powder is 1.5 μm; the rare earth fluoride is neodymium fluoride; the antioxidant is antioxidant 168; and the lubricant is magnesium stearate.
[0050] A method for preparing the high resistivity sintered NdFeB permanent magnet material comprises the following steps:
[0051] Step S1, smelting: putting the base alloy powder into a smelting furnace according to the composition formula, and when the vacuum degree in the smelting furnace is ≤3Pa, smelting, pouring, and sieving to obtain a strip sheet with an average thickness of 0.290mm;
[0052] Step S2, powder making: placing the strips prepared in step S1 in a hydrogen crushing furnace, evacuating the vacuum, filling with hydrogen and crushing the strips, and dehydrogenating at 520° C. for 5.5 hours to obtain coarse powder; then mixing the coarse powder with an antioxidant, and obtaining airflow-milled fine powder of the base alloy by airflow milling under nitrogen protection;
[0053] Step S3, powder mixing: the jet milled powder obtained in step S2 is uniformly mixed with rare earth fluoride powder, lubricant, aviation gasoline and nanomaterials, and then sieved by a sieving machine to reduce agglomeration of fine powder and improve the consistency of rare earth fluoride powder and nanomaterials at the grain boundary to obtain a mixed powder;
[0054] Step S4, molding: the mixed powder prepared in step S3 is pressed into a mold under a magnetic field, and isostatically pressed to obtain a compact;
[0055] Step S5, sintering: placing the green compact produced in step S4 into a vacuum sintering furnace, and sintering at 1020° C. for 7 hours to obtain a green compact;
[0056] Step S6, aging: The blank produced in step S5 is subjected to a three-level aging treatment to obtain a high resistivity sintered NdFeB permanent magnet material.
[0057] The smelting temperature in step S1 is 1475°C; the pouring temperature in step S1 is 1425°C; the average particle size of the airflow-milled powder of the base alloy in step S2 is ≤2.5μm, and D50 is ≤4.0μm.
[0058] The magnetic field strength of the magnetic field in step S4 is ≥ 2000 Gs; the isostatic pressing pressure in step S4 is 190 MPa, and the holding time is 20 s; the vacuum degree of the vacuum sintering furnace in step S5 is ≤ 0.05 Pa.
[0059] The first stage aging treatment temperature of the three-stage aging treatment in step S6 is 660° C. for 2.5 h, the second stage aging treatment temperature is 450° C. for 2.5 h, and the third stage aging treatment temperature is 470° C. for 2.5 h. Example 3
[0060] A high resistivity sintered NdFeB permanent magnet material is prepared from the following raw materials in parts by mass: 97.5 parts of base alloy fine powder, 3 parts of rare earth fluoride powder, 0.2 parts of antioxidant, 0.7 parts of lubricant, and 3 parts of aviation gasoline; the composition of the base alloy fine powder is (PrNd) a (TM)b (HM) c Ga d B e Fe 100-a-b-c-d-e , a=31, b=3, c=0.4, d=0.4, e=0.91, where TM is Co and HM is Hf.
[0061] The raw materials for preparing the high resistivity sintered NdFeB permanent magnet material also include: 0.3 parts of nanomaterial; the nanomaterial is nano-iron tetroxide; the particle size of the nanomaterial is 50nm; the particle size of the rare earth fluoride powder is 2.0μm; the rare earth fluoride is dysprosium fluoride; the antioxidant is antioxidant 1010; and the lubricant is zinc stearate.
[0062] A method for preparing the high resistivity sintered NdFeB permanent magnet material comprises the following steps:
[0063] Step S1, smelting: the base alloy powder is put into a smelting furnace according to the composition formula, and when the vacuum degree in the smelting furnace is ≤3Pa, smelting, pouring, and sieving to obtain a strip sheet with an average thickness of 0.295mm;
[0064] Step S2, powder making: placing the strips prepared in step S1 in a hydrogen crushing furnace, evacuating the vacuum, filling with hydrogen and crushing them, and dehydrogenating at 540° C. for 6 hours to obtain coarse powder; then mixing the coarse powder with an antioxidant, and using a jet milling process under nitrogen protection to obtain jet milled fine powder of the base alloy;
[0065] Step S3, powder mixing: the jet milled powder obtained in step S2 is uniformly mixed with rare earth fluoride powder, lubricant, aviation gasoline and nanomaterials, and then sieved by a sieving machine to reduce agglomeration of fine powder and improve the consistency of rare earth fluoride powder and nanomaterials at the grain boundary to obtain a mixed powder;
[0066] Step S4, molding: the mixed powder prepared in step S3 is pressed into a mold under a magnetic field, and isostatically pressed to obtain a compact;
[0067] Step S5, sintering: placing the green compact produced in step S4 into a vacuum sintering furnace, and sintering at 1030° C. for 9 hours to obtain a green compact;
[0068] Step S6, aging: The blank produced in step S5 is subjected to a three-level aging treatment to obtain a high resistivity sintered NdFeB permanent magnet material.
[0069] The smelting temperature in step S1 is 1485°C; the pouring temperature in step S1 is 1450°C; the average particle size of the airflow-milled powder of the base alloy in step S2 is ≤2.6μm, and D50 is ≤4.0μm.
[0070] The magnetic field strength of the magnetic field in step S4 is ≥ 2000 Gs; the isostatic pressing pressure in step S4 is 200 MPa, and the holding time is 35 s; the vacuum degree of the vacuum sintering furnace in step S5 is ≤ 0.05 Pa.
[0071] The first stage of the three-stage aging treatment in step S6 is performed at a temperature of 780°C for 3 hours, the second stage is performed at a temperature of 520°C for 3 hours, and the third stage is performed at a temperature of 490°C for 3 hours. Example 4
[0072] A high resistivity sintered NdFeB permanent magnet material is prepared from the following raw materials in parts by mass: 98.9 parts of base alloy fine powder, 4 parts of rare earth fluoride powder, 0.25 parts of antioxidant, 1 part of lubricant, and 4 parts of aviation gasoline; the composition of the base alloy fine powder is (PrNd) a (TM) b (HM) c Ga d B e Fe 100-a-b-c-d-e , a=32, b=4, c=0.7, d=0.45, e=0.92, wherein TM is a mixture of Al, Cu, Co, and Mn in a molar ratio of 1:1:2:1, and HM is a mixture of Nb, Zr, Hf, Ti, and V in a molar ratio of 1:1:2:3:1.
[0073] The raw materials for preparing the high resistivity sintered NdFeB permanent magnet material also include: 0.4 parts of nanomaterials; the nanomaterials are nano-tantalum silicide, nano-niobium carbide, and nano-ferroferric oxide mixed in a mass ratio of 1:3:5; the particle size of the nanomaterials is 70nm; the particle size of the rare earth fluoride powder is 2.5μm; the rare earth fluoride is praseodymium fluoride, neodymium fluoride, dysprosium fluoride, and terbium fluoride mixed in a mass ratio of 1:1:3:2; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 3:5; the lubricant is a mixture of zinc stearate and magnesium stearate in a mass ratio of 1:3.
[0074] A method for preparing the high resistivity sintered NdFeB permanent magnet material comprises the following steps:
[0075] Step S1, smelting: the base alloy powder is put into a smelting furnace according to the composition formula, and when the vacuum degree in the smelting furnace is ≤3Pa, smelting, pouring, and sieving to obtain a strip sheet with an average thickness of 0.302mm;
[0076] Step S2, powder making: placing the strips prepared in step S1 in a hydrogen crushing furnace, evacuating the vacuum, filling with hydrogen and crushing the strips, and dehydrogenating at 570°C for 6.5 hours to obtain coarse powder; then mixing the coarse powder with an antioxidant, and obtaining jet-milled fine powder of the base alloy by a jet milling process under nitrogen protection;
[0077] Step S3, powder mixing: the jet milled powder obtained in step S2 is uniformly mixed with rare earth fluoride powder, lubricant, aviation gasoline and nanomaterials, and then sieved by a sieving machine to reduce agglomeration of fine powder and improve the consistency of rare earth fluoride powder and nanomaterials at the grain boundary to obtain a mixed powder;
[0078] Step S4, molding: the mixed powder prepared in step S3 is pressed into a mold under a magnetic field, and isostatically pressed to obtain a compact;
[0079] Step S5, sintering: placing the green compact produced in step S4 into a vacuum sintering furnace, and sintering at 1040° C. for 11 hours to obtain a green compact;
[0080] Step S6, aging: The blank produced in step S5 is subjected to a three-level aging treatment to obtain a high resistivity sintered NdFeB permanent magnet material.
[0081] The smelting temperature in step S1 is 1500° C.; the pouring temperature in step S1 is 1470° C.; the average particle size of the airflow-milled powder of the base alloy in step S2 is ≤2.7 μm, and D50 is ≤4.0 μm.
[0082] The magnetic field strength of the magnetic field in step S4 is ≥ 2000 Gs; the isostatic pressing pressure in step S4 is 210 MPa, and the holding time is 50 s; the vacuum degree of the vacuum sintering furnace in step S5 is ≤ 0.05 Pa.
[0083] The first stage of the three-stage aging treatment in step S6 is at a temperature of 850° C. for 3.5 h, the second stage is at a temperature of 580° C. for 3.5 h, and the third stage is at a temperature of 500° C. for 3.5 h. Example 5
[0084] A high resistivity sintered NdFeB permanent magnet material is prepared from the following raw materials in parts by mass: 99.9 parts of base alloy fine powder, 5 parts of rare earth fluoride powder, 0.3 parts of antioxidant, 1.2 parts of lubricant, and 5 parts of aviation gasoline; the composition of the base alloy fine powder is (PrNd) a (TM) b (HM) c Ga d B e Fe 100-a-b-c-d-e, a=32.5, b=5, c=0.8, d=0.45, e=0.94, where TM is Mn and HM is Ti.
[0085] The raw materials for preparing the high resistivity sintered NdFeB permanent magnet material also include: 0.5 parts of nano material; the nano material is nano tantalum silicide; the particle size of the nano material is 80nm; the particle size of the rare earth fluoride powder is 3.0μm; the rare earth fluoride is terbium fluoride; the antioxidant is antioxidant 1010; and the lubricant is zinc stearate.
[0086] A method for preparing the high resistivity sintered NdFeB permanent magnet material comprises the following steps:
[0087] Step S1, smelting: putting the base alloy powder into a smelting furnace according to the composition formula, and when the vacuum degree in the smelting furnace is ≤3Pa, smelting, pouring, and sieving to obtain a strip sheet with an average thickness of 0.305mm;
[0088] Step S2, powder making: placing the strips prepared in step S1 in a hydrogen crushing furnace, evacuating the vacuum, filling with hydrogen and crushing them, and dehydrogenating at 580° C. for 7 hours to obtain coarse powder; then mixing the coarse powder with an antioxidant, and obtaining airflow-milled fine powder of the base alloy by airflow milling under nitrogen protection;
[0089] Step S3, powder mixing: the jet milled powder obtained in step S2 is uniformly mixed with rare earth fluoride powder, lubricant, aviation gasoline and nanomaterials, and then sieved by a sieving machine to reduce agglomeration of fine powder and improve the consistency of rare earth fluoride powder and nanomaterials at the grain boundary to obtain a mixed powder;
[0090] Step S4, molding: the mixed powder prepared in step S3 is pressed into a mold under a magnetic field, and isostatically pressed to obtain a compact;
[0091] Step S5, sintering: placing the green compact produced in step S4 into a vacuum sintering furnace, and sintering at 1050° C. for 12 hours to obtain a green compact;
[0092] Step S6, aging: The blank produced in step S5 is subjected to a three-level aging treatment to obtain a high resistivity sintered NdFeB permanent magnet material.
[0093] The smelting temperature in step S1 is 1505°C; the pouring temperature in step S1 is 1475°C; the average particle size of the airflow-milled powder of the base alloy in step S2 is ≤2.8μm, and D50 is ≤4.0μm.
[0094] The magnetic field strength of the magnetic field in step S4 is ≥ 2000 Gs; the isostatic pressing pressure in step S4 is 220 MPa, and the holding time is 60 s; the vacuum degree of the vacuum sintering furnace in step S5 is ≤ 0.05 Pa.
[0095] The first stage of the three-stage aging treatment in step S6 is 860°C for 4 hours, the second stage is 600°C for 4 hours, and the third stage is 510°C for 4 hours.
[0096] Comparative Example 1
[0097] A high resistivity sintered NdFeB permanent magnet material, which is substantially the same as Example 1, except that no nanomaterials and TM are added.
[0098] Comparative Example 2
[0099] A high resistivity sintered NdFeB permanent magnet material, which is substantially the same as Example 1, except that rare earth fluoride powder and HM are not added.
[0100] In order to further illustrate the beneficial technical effects of the high resistivity sintered NdFeB permanent magnet materials involved in the embodiments of the present invention, relevant performance tests were carried out on the high resistivity sintered NdFeB permanent magnet materials involved in Examples 1-5 and Comparative Examples 1-2. The test results are shown in Table 1. The test method is as follows: the comprehensive magnetic properties are detected according to the magnetic test method for permanent magnet (hard magnetic) materials in GB / T3217-2013; the resistivity test is carried out using a RESISTEST Ⅶ block resistance tester using a four-point probe method.
[0101] Table 1
[0102]
[0103] As can be seen from Table 1, the high resistivity sintered NdFeB permanent magnet material disclosed in the embodiment of the present invention has higher electrical conductivity than the comparative product and excellent comprehensive magnetic properties. The combined addition of nanomaterials, TM, rare earth fluoride powder and HM is beneficial to improving the above properties.
[0104] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions only describe the principles of the present invention. The present invention may be subject to various changes and improvements without departing from the spirit and scope of the present invention. These changes and improvements fall within the scope of the present invention. The scope of protection claimed by the present invention is defined by the attached claims and their equivalents.
Claims
1. A high resistivity sintered NdFeB permanent magnet material, characterized in that: The invention is prepared from the following raw materials in parts by weight: 95.0-99.9 parts of base alloy fine powder, 0.1-5 parts of rare earth fluoride powder, 0.1-0.3 parts of antioxidant, 0.2-1.2 parts of lubricant, 0.2-5 parts of aviation gasoline, and 0.1-0.5 parts of nanomaterials; the composition of the base alloy fine powder is (PrNd) a (TM) b (HM) c Ga d B e Fe 100-a-b-c-d-e , 29.5≤a≤32.5, 0<b≤5, 0<c≤0.8, 0.3≤d≤0.5, 0.88≤e≤0.94, wherein TM is one or more of Al, Cu, Co, and Mn, and HM is one or more of Nb, Zr, Hf, Ti, and V; the nanomaterial is at least one of nano-tantalum silicide, nano-niobium carbide, and nano-iron tetroxide; the particle size of the nanomaterial is 10-80nm; the particle size of the rare earth fluoride powder is 1.0-3.0μm; the rare earth fluoride is at least one of praseodymium fluoride, neodymium fluoride, dysprosium fluoride, and terbium fluoride; the average particle size of the base alloy fine powder is ≤2.8μm, and D50 is ≤4.0μm.
2. The high resistivity sintered NdFeB permanent magnet material according to claim 1, characterized in that: The antioxidant is at least one of antioxidant 1010 and antioxidant 168; the lubricant is one or more of zinc stearate and magnesium stearate.
3. A method for preparing the high resistivity sintered NdFeB permanent magnet material according to any one of claims 1-2, characterized in that: The steps include: Step S1, smelting: the base alloy fine powder is prepared according to the composition formula, and is put into a smelting furnace. When the vacuum degree in the smelting furnace is ≤3Pa, smelting, pouring, and sieving are performed to obtain a strip sheet with an average thickness of 0.285-0.305mm; Step S2, powder making: placing the strips prepared in step S1 in a hydrogen crushing furnace, evacuating the vacuum, filling with hydrogen and crushing, dehydrogenating at 500-580°C for 5-7h to obtain coarse powder; then mixing the coarse powder with an antioxidant, and obtaining jet-milled fine powder of the base alloy by a jet milling process under nitrogen protection; Step S3, powder mixing: the jet milled powder obtained in step S2 is uniformly mixed with rare earth fluoride powder, lubricant, aviation gasoline and nanomaterials, and then sieved by a sieving machine to reduce agglomeration of fine powder and improve the consistency of rare earth fluoride powder and nanomaterials at the grain boundary to obtain a mixed powder; Step S4, molding: the mixed powder prepared in step S3 is pressed into a mold under a magnetic field, and isostatically pressed to obtain a compact; Step S5, sintering: placing the green compact made in step S4 into a vacuum sintering furnace, and sintering at 1000-1050° C. for 6-12 hours to obtain a green compact; Step S6, aging: The blank produced in step S5 is subjected to a three-level aging treatment to obtain a high resistivity sintered NdFeB permanent magnet material.
4. The method for preparing the high resistivity sintered NdFeB permanent magnet material according to claim 3, characterized in that: The smelting temperature in step S1 is 1455-1505°C; the pouring temperature in step S1 is 1405-1475°C.
5. The method for preparing the high resistivity sintered NdFeB permanent magnet material according to claim 3, characterized in that: The magnetic field strength of the magnetic field in step S4 is ≥2000Gs; the isostatic pressing pressure in step S4 is 180-220Mpa, and the holding time is 5-60s; the vacuum degree of the vacuum sintering furnace in step S5 is ≤0.05Pa.
6. The method for preparing the high resistivity sintered NdFeB permanent magnet material according to claim 3, characterized in that: The first stage of the three-stage aging treatment in step S6 has an aging treatment temperature of 600-860°C and a time of 2-4h, a second stage of the aging treatment has an aging treatment temperature of 360-600°C and a time of 2-4h, and a third stage of the aging treatment has an aging treatment temperature of 450-510°C and a time of 2-4h.
Citation Information
Patent Citations
Rare-earth permanet magnet material with insulation performance
CN1048350C
Mesoporous-material-added zinc-plated neodymium-iron-boron magnet and preparation method thereof
CN106024239A
Sintered neodymium-iron-boron material containing Cu-M phase and preparation method of sintered neodymium-iron-boron material
CN115424800A
Cited By
High resistivity sintered neodymium-iron-boron magnet and method of making same
CN120581319B